2017
DOI: 10.1108/ijlss-03-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma applications in the textile industry: a case study

Abstract: Purpose The purpose of this study is to explore Lean Six Sigma (LSS) project and program success in the textile and apparel industry. This paper presents depictions of LSS implementations and the resulting economic impact for a textile company. Design/methodology/approach A qualitative approach consisting of a single descriptive case study and project document reviews was used. This method provided an in-depth view into what LSS means for one medium-sized global textile company and how it has proven importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Besides Brazil, the intensive adoption of case study also supports that LSS is in earlier stages of development around the world (Raval and Kant, 2017). Examples of LSS case studies researches were developed in India by Kumar et al (2006); Swarnakar and Vinodh (2016) and Chaurasia et al (2016), in the UK by Thomas et al (2009) and Dora and Gellynck (2015), in Taiwan by Cheng and Chang (2012), in The Netherlands by Gutierrez-Gutierrez et al (2016) and in the USA by Besseris (2014) and Adikorley et al (2017).…”
Section: Analysis and Discussion Of Reviewed Literaturementioning
confidence: 83%
“…Besides Brazil, the intensive adoption of case study also supports that LSS is in earlier stages of development around the world (Raval and Kant, 2017). Examples of LSS case studies researches were developed in India by Kumar et al (2006); Swarnakar and Vinodh (2016) and Chaurasia et al (2016), in the UK by Thomas et al (2009) and Dora and Gellynck (2015), in Taiwan by Cheng and Chang (2012), in The Netherlands by Gutierrez-Gutierrez et al (2016) and in the USA by Besseris (2014) and Adikorley et al (2017).…”
Section: Analysis and Discussion Of Reviewed Literaturementioning
confidence: 83%
“…Firstly, the SS was used in the manufacturing sector: Adikorley et al applied it in the textile industry (Adikorley et al, 2017) while Besseris et al made an application in the food industry (Besseris et al, 2014). Many researchers have conducted systematic review to explore the methodology from different perspectives: Bakar et al reviewed all the critical factors of success of the methodology (Bakar et al, 2015) while, recently, Chugani et al investigated the application of this methodology from a green research perspective (Chugani et al, 2017), Freitas et al studied the impact of the methodology on the organizational sustainability (Freitas et al, 2017) and Walter and Paladini identified the main directions for future research (Walter and Paladini, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several manufacturing organizations in both developed and emerging economies use either TPM or TQM exclusively whereas others implement an integrated TQM and TPM, based upon their understanding of manufacturing fundamentals and business priorities. It has been documented that such quality and maintenance management practices, when utilized as a business operations management strategy exclusively, have provided manufacturing firms with a competitive advantage to survive in a global market (Adikorley et al, 2017;Chaurasia et al, 2016;Konecny and Thun, 2011;Sunder, 2016). Every year, many research articles are published dealing with the separate implementation of either quality management or maintenance management methodologies in both manufacturing and service sectors.…”
Section: Introductionmentioning
confidence: 99%